Speaking with their own voices : the stories of slaves in the Persian Gulf in the 20th century - Zdanowski, Jerzy, 1949- (Cambridge Scholars Publishing, 2014)
This book presents an analysis of the slavery and manumission practiced in the Persian Gulf region in the first half of the 20th century. It is unique as it exposes the life stories of several hundred slaves, speaking with their own voices. A striking aspect of the majority of studies on slavery is that they provide the reader with excellent statistics and describe the mechanism of enslavement, the routes of slave trading, and the economic and social conditions of enslaved people, but slaves ...